In vitro acetylcholinesterase and butyrylcholinesterase inhibitory potentials of essential oil of Artemisia macrocephala - Shoaib, Mohammad; Shah, Ismail; Ali, Niaz; Shah, Syed Wadood Ali (Bangladesh Journal of Pharmacology, 2015)
In this study we screened the essential oil of Artemisia macrocephala for acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory potentials. Ellman's assay method was used to investigate the enzyme inhibitory potential of the essential oil. The oil sample showed 87.7 ± 1.2, 77.9 ± 0.6, 74.5 ± 1.9 and 62.5 ± 0.3 percent AChE inhibition at 1000, 500, 250 and 125 ?g/mL concentrations respectively with IC50 value of 40 ?g/mL. Similarly it showed 81.8 ± 0.6, 75.6 ± 1.2, 70.0 ± 0.6 and 64.2 ± 1.4 percent BChE inhibition in 1000, 500, 250 and 125 ?g/mL concentrations respectively with IC50 value of 30 ?g/mL. The results of this study confirm the beneficial applications of the oil sample in the treatment of various neurodegenerative disorders including Alzheimer's disease, Parkinson's disease, ataxia and all other forms of dementia.